KONTRIBUSI KH. ALI MUSTAFA YAQUB DALAM MENGKONTEKSTUALISASIKAN HADIS DI INDONESIA - Yusi Yuliandini; Hidayati Hidayai (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
Islam has regulated that in understanding science, especially religious knowledge, it requires the guidance of a teacher who has good credibility, especially in undrstanding the hadith spread in Indonesia. Because the power that the word